PENGEMBANGAN KOMIK ELEKTRONIK MENGGUNAKAN IBIS PAINT X MATERI MARI BELAJAR QURAN SURAT AL – FIIL - Yuliana Alyas; Resyi A. Gani; Rukmini Handayani (STKIP Subang, 2023)
ABSTRACT In learning, educators should use learning media that can motivate students' enthusiasm for learning. However, based on the results of observations and interviews at SDN Pajajaran, Bogor City, it was found that educators had not used instructional media as a tool to motivate learning enthusiasm. The purpose of this study was to develop electronic comic learning media using Ibis Paint X to create interesting and motivating learning media for students. This study used the R&D method with the ADDIE approach. The research was carried out in five stages, namely the stages of needs analysis, design, development, implementation and evaluation. The subject of this study was fourth grade students at SDN Pajajaran, Bogor City. The feasibility of the developed media product can be proven from the percentage of media experts 85%, linguists 92%, and material experts 96% in the